Media education and educational commons for youth civic engagement. A case study from the Horizon 2020 project SMOOTH - Cappello, Gianna; Siino, Marianna (Frontiers in Sociology, 2023)
This study presents the preliminary findings of the first round of implementation of a case study included in the Horizon 2020 project SMOOTH. The project's main objective is to introduce and study the emergent paradigm of the educational commons as an alternative system of values and actions for promoting intercultural and intergenerational dialogue and establishing spaces of democratic citizenship that support the development of local communities. Our case study adopts this paradigm with insights derived from the field of media education. Hence, our research questions were as follows: (a) How do young people collectively experience and build the educational commons? (b) How do participants (youth and adults) in educational commons experience peer governance and how do they handle and resolve conflicts? (c) How does the co-creation of a photo-blog as a shared space of work help young people discover and develop a "civic intentionality" in the (digital) public sphere? (d) What are the effects of applying a commons' logic to address inequalities and achieve social inclusion of young people from vulnerable social groups? Fieldwork, framed in an ethnographic and action-research approach, was developed by examining the three dimensions of the notion of educational commons (commoners, commoning practices, and community). Although data collection and analysis are still in progress, our preliminary results allow us to draw some initial reflections on what worked well in the first round and what could hinder the achievement of the project's objectives. We also propose hypotheses for re-designing the second round to overcome the weaknesses that emerged during the first experimental phase and foster its strengths.